2004
DOI: 10.1080/09546630410035329
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy consisting of week pulses of oral terbinafine plus topical application of terbinafine cream in the treatment of onychomycosis

Abstract: Favorable treatment outcome was gained from this terbinafine 1-week pulse regimen and also better compliance compared with a standard daily regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…When terbinafine is given orally at a dosage of 250 mg day −1 for 6–12 weeks, it persists in the nail plate for an additional 30–36 weeks at concentrations above the minimum inhibitory concentrations of several dermatophyte species 3 . Researchers have hypothesized that pulse therapy with terbinafine should be effective for treatment of onychomycosis 4–9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When terbinafine is given orally at a dosage of 250 mg day −1 for 6–12 weeks, it persists in the nail plate for an additional 30–36 weeks at concentrations above the minimum inhibitory concentrations of several dermatophyte species 3 . Researchers have hypothesized that pulse therapy with terbinafine should be effective for treatment of onychomycosis 4–9 …”
Section: Discussionmentioning
confidence: 99%
“…Sanmmano et al. [8] reported that combination of pulse therapy with terbinafine 250 mg and daily application of topical terbinafine cream achieved good results and provided good patient compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these facts, it would be interesting to know whether or not pulse therapy with terbinafine is also effective. In this, some clinical trials have reported favorable results by intermittent dosing of terbinafine 4–8,12–14 …”
Section: Discussionmentioning
confidence: 99%
“…Sanmmano et al. reported that combination of pulse therapy with terbinafine 250 mg and topical terbinafine cream achieved good results and provided good patient compliance 7 . Zaias et al.…”
Section: Discussionmentioning
confidence: 99%